A spectroscopic experimental and semi-empirical study of [Eu(salen)2] as a red-emitter for phosphor-converted UV LED - Mutti, A. M.G. [UNESP]; Canisares, F. S.M. [UNESP]; Machini, W. B.S. [UNESP]; Pires, A. M. [UNESP]; Teixeira, M. F.S. [UNESP]; Lima, S. A.M. [UNESP] (Elsevier, 2021)
Most of commercial WLEDs have a lack of red-emission component resulting in cool white illumination. Aiming this issue, in this paper, we present the synthesis of [Eu(salen)2] with a Schiff base type ligand, the salen (N,N′-ethylene-bis(salicylidenimine)), another lanthanide complex was also investigated, the [Gd(salen)2]. Both complexes were characterized by conventional spectroscopy techniques to confirm their preparation, and the free software LUMPAC was used as a friendly interface to determine the experimental intensity parameters (Ω2 and Ω4) for the Eu-complex, it was also used to optimize the complex structure, perform theoretical calculations of excited states, and intensity parameters. The Eu-complex was immobilized in PMMA films in different amounts, and their photophysics properties were analyzed. The 7.5 wt% doped film showed the best photophisical results (τ = 0.226 ms; ΦEuEu = 9.61%), and it was chosen to coat a UV LED-chip (λem = 400 nm ± 10 nm) to fabricate a red emissive LED-prototype; also, a prototype with a blend between powdered Eu-complex and cyanoacrylate glue was fabricated, and their emission behavior and radiant photostability were compared. The prototype with the doped PMMA film exhibited poorer radiant photostability than the powder prototype after 24 h of operation. Thus, the [Eu(salen)2] powder prototype gather some important characteristics to be used as a red component of warm WLEDs.
Keywords: Europium(III); Lanthanide; Rare earth; Schiff base; Theoretical calculation; WLEDs